Trajetórias religiosas: percursos de pais e mães de santo do candomblé em João Pessoa - Medeiros, Gracila Graciema de (2016)
Studying religious trajectories of parents and Candomblé holy mothers in Joao Pessoa, constituted the subject of this research aimed to understand specific elements of religious transit in the city of João Pessoa, from the search and adhesion to Candomblé. For this, there are trajectories of religious life and the movement of each track, in and out of african-Brazilian field five players, parents and Candomblé holy mothers. Dialogue with praxiological Bourdieu's sociology was the anchor point of reflection, which, however, did not shy away from you direct any criticism. The concepts of habitus, field and track become central to the four descriptive and analytical, so as the assumptions of sociology who use the concepts of socializing experiences and provisions. This research is characterized as a qualitative research, with data collected through semiestrutura interview, and enriched by the experience of the researcher who for almost ten years is part of the daily life of a yard of Candomble, and communing of its significant symbols and values the african-Brazilian religious field in Joao Pessoa. The analysis of the trajectories of the subjects builds a policy pathway as an individual, which, however, continually shows crossed by social forces, disputes, conflicts, changes and trends working in the field in question.